Pillar BNCO nanoflake/nanorod hybrid networks synthesized by plasma-enhanced hot filament CVD: Structure and photoluminescence. (July 2017) - Wang, B.B.; Shao, R.W.; Qu, X.L.; Levchenko, I.; Keidar, M.; Zhong, X.X.; Zheng, K.; Xu, S.; Ostrikov, K.
Abstract: Theoretical studies of the complex, doped BN/carbon pillar hybrid networks have revealed their great potential for energy and power conversion, nanoelectronics, optoelectronics and electric propulsion devices. Demonstration of the technique to synthesize such networks and control the structure is critical for their applications. Here we report on the successful fabrication of complex, hybrid pillar networks consisting of carbon- and oxygen-doped BN nanoflakes and nitrogenated carbon nanorods. The complex, hybrid, structure-controlled pillar networks were grown directly on the carbon nanorods in N2 -H2 plasma using B4 C as the boron and carbon sources. The characterization by scanning and transmission electron microscopy, micro-Raman, Fourier transform infrared and X-ray photoelectron spectroscopies has confirmed that the carbon- and oxygen-doped BN crystalline nanoflakes indeed grow on the amorphous nitrogenated carbon nanorods and form the pillar hybrid networks. The photoluminescence measurements have revealed that the pillar hybrid networks generate ultraviolet, blue, green, and red photoluminescence bands. In particular, the photoluminescence properties of the pillar hybrid networks can be effectively tuned by changing the network structure. These outcomes can contribute to the synthesis of novel nanostructures and the development of next generation optoelectronic nanodevices and power devices. Graphical abstract: